The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph192416809
|View full text |Cite
|
Sign up to set email alerts
|

Metal Exposure-Related Welder’s Pneumoconiosis and Lung Function: A Cross-Sectional Study in a Container Factory of China

Abstract: Long-term inhalation of welding fume at high exposure can cause welder’s pneumoconiosis, and metals in welding dust are associated with respiratory dysfunction. This cross-sectional study, which contains 384 Chinese male workers who were or had been working in a container factory, aimed to assess the potential risk of haemal and urinary metal content in welder’s pneumoconiosis. Further, we investigated their effects on lung function parameters. Metal content and lung function were measured using inductively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In a study conducted with Zhou et al, there were a signi cant association between lung function indices in the welder's pneumoconiosis and ambient concentration of metals. The results also showed that Cr and Zn had an important role in welder's pneumoconiosis (Zhou et al 2022b). So, it is clearly evident that the increase of fumes in the ambient air of welding is a main health threat.…”
Section: The Concentration Of Welding Fumesmentioning
confidence: 86%
“…In a study conducted with Zhou et al, there were a signi cant association between lung function indices in the welder's pneumoconiosis and ambient concentration of metals. The results also showed that Cr and Zn had an important role in welder's pneumoconiosis (Zhou et al 2022b). So, it is clearly evident that the increase of fumes in the ambient air of welding is a main health threat.…”
Section: The Concentration Of Welding Fumesmentioning
confidence: 86%
“…One study found that cough and phlegm symptoms were more likely to be related to an obstructive pattern than wheeze or phlegm 60) . Notwithstanding, another respiratory study found that automotive welders have a restrictive lung pattern 61) . This is because one of the things that can cause abnormal lung patterns in workers (either obstructive or restrictive) is how they work and what they are exposed to at work.…”
Section: Resultsmentioning
confidence: 99%
“…asthma or chronic bronchitis) (1). In a case report from 2022, Cha E.-W. et al described the situation of a 54 year-old man, presenting multiple episodes of severe MMF aggravated by chemical pneumonitis induced by the inhalation of zinc-oxide fumes, after arc welding galvanized steel in a poorly ventilated area (13).…”
Section: Pneumoconiosismentioning
confidence: 99%